Keselamatan dan kesehatan kerja nelayan pengguna kompresor - Dini Karina Mawarni Sualang; Revols D.Ch. Pamikiran; Lefrand Manoppo; Alfret Luasunaung; Ivor L Labaro; Fransisco P.T. Pangalila (Universitas Sam Ratulangi, 2024)
This study aims to examine the safety and health aspects of fishermen who use compressors. This research is a descriptive study to describe the use of compressors as a diving aid and its impact on the lives of fishermen. Data collection methods were carried out through surveys and interviews, as well as using questionnaires. The process of data processing and analysis was carried out through the use of cross-tabulation and presentation in the form of pictures, diagrams, and histograms. Several things can be conveyed as a result of this study, namely: the use of compressors as a breathing aid is very dangerous to health because it does not follow the existing diving rules such as diving procedures and the use of air filtering filters that are not used, and the accumulation of negative impacts on the safety of fishermen’s lives, and there have been several fishermen who have died.